The impact of monetary policy on economic growth in the context of globalization - Jiang Fu (GREEN ECONOMY AND DEVELOPMENT, 2024)
This article examines the impact of monetary policy on economic growth in the context of globalization. It explores the key types and instruments of monetary policy, including expansionary and contractionary policies, interest rates, and open market operations. Case studies from the United States, the European Central Bank, and Japan illustrate the influence of global economic events on national economies.